Detection and genomic characterization of Ndumu virus in Coastal Kenya from Culex and Mansonia africana mosquitoes - Wanjiru, Tabitha; Bulimo, Wallace; Langat, Solomon; Kinyua, Johnson; Yalwala, Santos; Kerich, Gladys; Ambale, Janet; Garges, Eric; Haynes, Robert; Kellar, Gerald; Eads, John; Eyase, Fredrick (Frontiers in Virology, 2025)
IntroductionAlphaviruses, members of the family Togaviridae, are globally distributed arthropod-borne viruses, including several medically significant pathogens such as Chikungunya virus and Sindbis virus. These viruses are primarily transmitted by mosquitoes and can cause a wide range of diseases in humans and animals, from febrile illnesses to neurological conditions. While many alphaviruses have been extensively studied, others, like Ndumu virus (NDUV), remain poorly understood. Surveillance of these viruses, is essential for monitoring their circulation within mosquito populations, enabling early detection and informed public health responses. This study sought to conduct comprehensive surveillance of pathogenic viruses in mosquito populations in North-eastern and coastal Kenya, during which NDUV was detected and characterized.MethodsAdult mosquitoes were collected from Kwale, Malindi, Mombasa, and Isiolo counties using light traps. A total of 14,106 mosquitoes were grouped into 1,597 pools by species and geographic origin. Cell culture was conducted using Vero E6 cell line, followed by RNA extraction, library preparation, and sequencing with the Illumina MiSeq platform. Preliminary analysis was performed on the CZ-ID platform. Raw sequence reads underwent quality control with PrinseqLite v0.20.4 to remove adapters and filter low-quality reads. De Novo assembly was conducted using MEGAHIT v1.2.9, and final contigs were analyzed using BLASTn against the NCBI nucleotide (nt) database. Phylogenetic analysis was performed using the Maximum Likelihood method.ResultsTwo pools from Malindi and one pool from Kwale showed cytopathic effects in four subsequent passages. NDUV was confirmed in pools with Culex annulioris, Mn. Africana and Culex univittatus species. Genomic analysis revealed lengths of 11,632, 11,646 and 11,646 nucleotides for the isolates. Phylogenetic analysis placed these isolates within the alphavirus clade, closely related to other NDUV strains.DiscussionThis detection underscores the importance of routine arbovirus surveillance to better understand the circulation and dynamics of neglected viruses like NDUV within endemic regions. Even though there exists serological evidence of exposure in humans, NDUV has not been directly linked to human or animal disease. The current data raises questions about its zoonotic potential and possible role as an emerging pathogen.